Impacts of Cognitive Conflict-Integrated Teaching Material on Student’s Conceptual Understanding and Learning Motivation in Light Wave Learning - Intan Cahya Nusli; Fatni Mufit; Asrizal Asrizal; Dea Stivani Suherman (Universitas Negeri Padang, 2026)
Physics learning on the topic of light waves continues to face several challenges, including low conceptual understanding, persistent misconceptions, and insufficient student learning motivation. This study investigated the effectiveness of cognitive conflict-based teaching materials integrated with Augmented Reality (AR) in improving students’ conceptual understanding and learning motivation. A quantitative quasi-experimental approach with a nonequivalent pretest–posttest control group design was employed. Data were collected using a four-tier multiple-choice test and an ARCS-based learning motivation questionnaire and analyzed using descriptive statistics and the Mann–Whitney U test. The results showed that students in the experimental group achieved a higher level of conceptual understanding (80.5%) than those in the control group (48.0%), accompanied by a greater reduction in misconceptions. Significant differences were also found in both conceptual understanding and learning motivation between the two groups (p < 0.05). These findings suggest that cognitive conflict-based teaching materials integrated with AR are effective in improving conceptual understanding and learning motivation and can serve as an innovative alternative for physics learning.